Menggagas Era Baru Pendidikan Islam 4.0 yang Visoner - Samsul Bahri (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2019)
This paper discusses the idea of a new era of visionary Islamic education 4.0, this study is a philosophical normative, and philosophical, substantial approach. The method used is analytical descriptive supported by authoritative sources. This study offers an offer on Islamic education to get out of the problems of Islamic education that occur in its implementation, both the dichotomy of science, exclusivism, and only in the form of teaching that does not teach students. So this paper proves the importance of a new era of Islamic education that follows the 4.0 industrial revolution by participating in self-discipline by creating non-dichotomic education, inclusivism, and changing from teaching to learning, with a digital basis so that Islamic education is able to develop its potential, and learn to complete all life problems or with the term learning how to learn.